2022
DOI: 10.16995/glossa.8026
|View full text |Cite
|
Sign up to set email alerts
|

Affrication as the cause of /s/-retraction: Evidence from Manchester English

Abstract: Retraction of /s/ to a more [ʃ]-like sound is a well-known sound change attested across many varieties of English for /stɹ/ words, e.g. street and strong. Despite recent sociophonetic interest in the variable, there remains disagreement over whether it represents a case of long-distance assimilation to /ɹ/ in these clusters or a two-step process involving local assimilation to an affricate derived from the sequence /tɹ/. In this paper, we investigate Manchester English and apply similar quantitative analysis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The focus of the present study is /s/-retraction, a sound change in progress in many varieties of English by which /s/ approaches /S/ in the context of /r/, most notably in /str/ clusters 2 So for a speaker exhibiting /s/-retraction, a word like street /strit/ may sound more like shtreet /Strit/. This has been observed in various dialects of American English (Shapiro, 1995;Durian, 2007;Baker et al, 2011;Gylfadottir, 2015;Wilbanks, 2017;Smith et al, 2019;Phillips, 2020) as well as varieties of English across the Anglophone world (Lawrence, 2000 for New Zealand;Glain, 2013;Bailey et al, 2022 for the United Kingdom; Stevens and Harrington, 2016 for Australia). Additionally, corpus studies have demonstrated that /s/-retraction is advancing in apparent time in the United States (Gylfadottir, 2015;Wilbanks, 2017).…”
Section: Introductionmentioning
confidence: 98%
“…The focus of the present study is /s/-retraction, a sound change in progress in many varieties of English by which /s/ approaches /S/ in the context of /r/, most notably in /str/ clusters 2 So for a speaker exhibiting /s/-retraction, a word like street /strit/ may sound more like shtreet /Strit/. This has been observed in various dialects of American English (Shapiro, 1995;Durian, 2007;Baker et al, 2011;Gylfadottir, 2015;Wilbanks, 2017;Smith et al, 2019;Phillips, 2020) as well as varieties of English across the Anglophone world (Lawrence, 2000 for New Zealand;Glain, 2013;Bailey et al, 2022 for the United Kingdom; Stevens and Harrington, 2016 for Australia). Additionally, corpus studies have demonstrated that /s/-retraction is advancing in apparent time in the United States (Gylfadottir, 2015;Wilbanks, 2017).…”
Section: Introductionmentioning
confidence: 98%